Comment: Emotional and Autonomic Arousal Constructs in Psychophysiological Research: Where Do We Go From Here?. (January 2016) - Norman, Greg J.
Picard, Fedor, and Ayzenberg (2016) provide a review of the existing literature on the relationship between electrodermal activity (EDA) and affective processes and present data from a number of studies suggesting strong lateralization in EDA reactivity to emotion. As the authors note, their manuscript extends previous work suggesting the concept of arousal is more complex than previously thought, and they provide a framework for interpreting such complexities within the context of a multiple arousal theory.